The Relation of Foot Morphology to Performance in Three Vertical Jumping Tasks [Relación Entre la Morfología del Pie y el Rendimiento en Tres Saltos Verticales] - Alarcon-Alvarez, E; Sanchez-Ramirez, C; Hormazabal-Aguayo, I (Universidad de la Frontera, 2020)
The objective of this research is to relate the performance in three vertical jump events with morphological variables of the foot and stature. A total of 177 practitioners of 12 sporting events aged 24.5 ±8.0 years, with 71.01 ±13.00 kg of body mass, 1.71±0.09 m height, and BMI of 24.29±3.24 kg·m-2 were evaluated with an anthropometer in terms of foot length (FL), forefoot width (FW), navicular height (NH), and hindfoot width (HW). These variables were normalized to the height of the subjects. From the footprint record the arch index (AI) was obtained, which indicates the morphology of the medial longitudinal foot arch (MLFA). Performance was evaluated in three vertical jump events: countermovement jump (CMJ), squat jump (SJ), and drop jump (DJ), recording the height reached. FL, FW and HW show a weak positive correlation (r<0.4; p<0.05) with the heights achieved in the three types of jump. The stature is strongly associated with FL, FW and HW (r=0.8; r=0.7 and r=0.6; respectively; p<0.05) and with the height in CMJ, SJ, and DJ (r=0.37; r=0.41 and r=0.32, respectively, p<0.05). The only normalized morphological foot variable that maintained consistency in the correlations analysis was the normalized foot length (NFL) with CMJ (r = 0.2, p<0,05). The subjects whose left foot length was equivalent to 14 % of the stature jumped 27.94 ±6.63 cm, those with 15 % jumped 30.96 ±7.4 cm, and those with 16 % jumped 31.03 ±7.8 cm. FL, FW, HW, and stature are moderately correlated with performance in vertical jump events. However, after discarding the stature of the subjects, only the foot length maintained its relation with performance in CMJ. © 2020, Universidad de la Frontera. All rights reserved.